MANAGEMENT OF A PATIENT WITH A SECRETORY FORM OF AZOOSPERMIA - Бушмакин, Алексей Дмитриевич; Луговой, Константин Александрович; Помешкин, Евгений Владимирович; Тришкин, Алексей Геннадьевич; Курганова, Лилия Владиславовна; Зуева, Галина Павловна; Лесников, Антон Игоревич; Бочкарникова, Асмик Гербертовна; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2022)
Violation of male reproductive health is one of the most urgent problems for scientific research at the present time and is both a reflection of the quality of medical care and an indicator of overall well-being. One of the most difficult for the diagnosis and treatment of pathospermia is azoospermia. This pathological condition manifests itself in the complete absence of spermatozoa in the ejaculate during a two-time examination of centrifuged sperm with a targeted search for spermatozoa. Azoospermia is detected in approximately 7-10 % of all patients with impaired reproductive function. This clinical case clearly illustrates the tactics of differential diagnosis of a patient with azoospermia, and shows the importance of histological conclusion for predicting the effectiveness of therapy and achieving clinical pregnancy. In this case, a testicular biopsy served as a reason for prolonging therapy, and allowed to achieve a clinical pregnancy. Correctly chosen tactics allowed.
Keywords: infertility; azoospermia; ovarian biopsy